Human trafficking : a global perspective - Shelley, Louise I. (Cambridge, UK : Cambridge University Press, 2010)
'This book examines all forms of human trafficking globally, revealing the operations of the trafficking business and the nature of the traffickers themselves'-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Human trafficking